Contribution of Village Funds to Regional Economic Recovery in South Sulawesi Province - Karim, Abdul; Ruslan, Muhlis; Burhanuddin, Andi; Taibe, Patmawaty; Sobirin, Sobirin (SEIKO : Journal of Management & Business, 2023)
In 2022, it will be a period of sustainable economic recovery in all sectors after the Covid-19 Pandemic. The state revenue and expenditure budget are the primary and leading instrument in growing the national economy that is timely, effective, and on target. The government has set a village fund ceiling of IDR 68 trillion. The village funds are distributed to 74,960 villages spread across 434 districts/cities throughout Indonesia. The realization of the distribution of transfers to regions and village funds in South Sulawesi until August 2022 reached IDR 19.23 trillion or 55.26% of the ceiling of IDR 29.22 trillion. The most significant contribution lies in the general allocation fund, which is IDR 12.96 trillion. This figure is even higher than the previous year's period which reached IDR 12.84 trillion. In the total budget provided, each village receives an average of IDR 907.1 million. The Covid-19 pandemic, which has hit the economy in the last 2 years, has forced the government through state revenue and spending budget instruments to work hard to overcome the impact caused by the pandemic. This can be seen from the policy of transferring funds to the regions and village funds for 2022 which are directed at supporting social protection programs for the poorest and most vulnerable people. The nation's economic recovery must rely on community empowerment in the community-based economy. South Sulawesi Province has 21 Regency and 3 Cities, 307 Sub-districts, and 2,255 villages. South Sulawesi's economy in the second quarter of 2022 continued its positive performance with increased growth compared to the previous quarter. South Sulawesi's economy recorded growth of 5.18%, higher than the previous quarter which grew 4.28%. Residents of rural communities in South Sulawesi Province have dominant livelihoods in the agricultural, forestry, and fisheries sectors (. In villages where the main income of most the population is agriculture, forestry, and fisheries, 64% of the villages have rice as the subsector commodity. Kata Kunci: Village fund; Regional economic recovery; South Sulawesi Province